Relationship between functional classification levels and anaerobic performance of wheelchair basketball athletes - Molik, B.; Laskin, J. J.; Kosmol, A.; Skucas, K.; Bida, U. (Research Quarterly for Exercise and Sport, 2010)
Wheelchair basketball athletes are classified using the International Wheelchair Basketball Federation (IWBF) functional classification system. The purpose of this study was to evaluate the relationship between upper extremity anaerobic performance (AnP) and all functional classification levels in wheelchair basketball. Ninety-seven male athletes from the Polish and Lithuanian national wheelchair basketball leagues took part in this study. The Wingate Anaerobic Test was used to assess four AnP indexes with an arm crank ergometer. The level of AnP in wheelchair basketball athletes depends to some degree on classification level. No significant differences were found for the AnP indexes across levels 1.0-2.5 and 3.0-4.5. However, the AnP level for those in classes 1.0-2.5 was significantly lower than those in classes 3.0-4.5. The findings from this study provided some evidence that the IWBF functional classification system should be reexamined and that a consolidation of the current eight levels might be in order.